From Vulnerability to Disclosure: A Normative Approach to Understanding Trust in Obstetric and Intrapartum Nurse-Patient Communication. Issue 5 (16th April 2021) - Dalton, Elizabeth D.; Pjesivac, Ivanka; Eldredge, Scott; Miller, Laura
ABSTRACT: This study qualitatively examined how nurses, nurse practitioners, and nurse midwives construct the meaning of patient trust in their work caring for pregnant and laboring women. Twenty-two interviews were conducted with nurse participants employed at clinics, hospitals, and birth centers across Southeastern United States. Using a normative theoretical approach within the multiple goals framework, we identified five emergent themes that characterize trust as it shapes nurses' communicative goals: trust as the woman's acceptance of vulnerability and risk, the woman relinquishing control, the woman conceding to the nurse's expertise, the woman feeling heard, and the woman's disclosure of information. The results support previous studies, which conceptualized trust as vulnerability, risk, and disclosure whereas the remaining themes are original to this study. The results are interpreted both in light of existing links between trust and communication and the shifting and conflicting goals of nurses as they attempt to achieve their primary goal of optimal health outcomes. Passive constructions of trust that conflate it with women's acquiescent behaviors could have implications for the quality of communication between nurses and patients. In addition, trust, as understood by these participants, becomes situated as an instrumental means to achieving patient cooperation and desired health outcomes rather than a relational goal that supports women's agency throughout obstetric and intrapartum processes. This may be at odds with the modern movement toward patient-centered care and shared decision-making in U.S. maternity care.